Morphodynamics of Cold High Latitude Semiarid Regions: The Example of Ellef Ringnes Island, Nunavut - St-Onge, Denis; Gullentops, Frans (Géographie physique et Quaternaire, 2005)
AbstractIn this paper we use the example of Ellef Ringnes Island, Nunavut, to examine active geomorphic processes in a high latitude semiarid region. The spectacular landscape of Ellef Ringnes Island is principally the result of fluvial erosion controlled by geological structure. The nival regime concentrates flow in a brief late-spring period which provides strong erosive capabilities for rivers in spite of low annual precipitation. Other processes related to the cold environment produce a variety of minor landforms such as patterned ground, mud flows associated with ground ice, and solifluction lobes.